EVALUASI KINERJA CAMPURAN ASPAL DENGAN SUBTITUSI LIMBAH PLASTIK PET DALAM MENINGKATKAN DURABILITAS CAMPURAN ASPAL PENETRASI 60/70 TEHADAP VARIASI LAMA WAKTU PERENDAMAN - Fadhil, Ammar; Khairunnisa, Hanyta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
ABSTRACTThe utilization of plastic waste can be done by using it as an additive in asphalt concrete wearing course (AC-WC) mixtures. Incorporating plastic waste into road construction serves two purposes: reducing plastic waste and enhancing road quality. This research aims to determine the durability value when 7% PET plastic is immersed at 60°C for 0.5 hours, 24 hours, 36 hours, 48 hours, and 72 hours in a 60/70 penetration asphalt mixture. This study was conducted by adding PET pieces in a dry condition. The Optimal Asphalt Content (OAC) obtained from the test specimen was 6.29% (Marwati et al., 2021). From the Marshall test results without PET, the 24-hour durability value was 94.13%, and with the addition of 7% PET, the durability value at 24 hours increased to 96.16% and at 36 hours to 91.57%, meeting the specification of ≥ 90%, while at 48 hours it was 83,31%, and at 72 hours it was 80,70% which did not meet the requirements. The stability value increased due to the addition of PET in the asphalt mixture compared to the asphalt mixture without PET. The addition of 7% PET still met the requirements for a 36-hour immersion time in water with a stability value of 1094.13 kg, and Marshall parameters such as VIM 4.83%, VFA 79.41%, VMA 23.17%, MQ 288.57 kg/mm, and flow 3.80 mm met the specifications of Bina Marga 2020.